Ibrutinib and rituximab plus cyclophosphamide, doxorubicin, vincristine and prednisone in patients with previously untreated non‐germinal centre B‐cell‐like diffuse large B‐cell lymphoma: A Chinese subgroup analysis of the phase III PHOENIX trial. Issue 4 (30th August 2022) - Zhu, Jun; Hong, Xiaonan; Song, Yu Qin; Hodkinson, Brendan; Balasubramanian, Sriram; Wang, Songbai; Zhang, Qingyuan; Shi, Yuankai; Huang, Huiqiang; Zhang, Huilai; Zhu, Yan; Shreeve, Stephen Martin; et al.
Abstract: In this post hoc subgroup analysis of 200 patients enrolled in China from the phase III PHOENIX trial ( N  = 838, NCT01855750), addition of ibrutinib to rituximab plus cyclophosphamide, doxorubicin, vincristine and prednisone (R‐CHOP) did not improve event‐free survival (EFS) versus placebo+R‐CHOP in the intent‐to‐treat (ITT; n  = 200, hazard ratio [HR] = 0.83, 95% confidence interval [CI]: 0·509–1.349; p  = 0.4495) or activated B‐cell‐like (ABC; n  = 141 [based on available gene‐expression profiling data], HR = 0.86, 95% CI: 0.467–1.570; p  = 0.6160) subpopulations. However, ibrutinib+R‐CHOP improved EFS (HR = 0·50, 95% CI: 0.251–1.003) and progression‐free survival (PFS; HR = 0.48, 95% CI: 0.228–1.009) versus placebo+R‐CHOP in patients aged <60 but not ≥60 years. Grade ≥3 serious treatment‐emergent adverse events occurred more with ibrutinib+R‐CHOP (45·6% vs. 31·3%). The percentage of patients receiving ≥6 cycles of R‐CHOP was similar across treatment arms in those <60 years. A numerical trend was seen towards improved EFS and PFS with ibrutinib+R‐CHOP versus placebo+R‐CHOP in patients with MYC ‐high/ BCL2 ‐high co‐expression. In this slightly younger Chinese subgroup, ibrutinib+R‐CHOP did not improve EFS in the ITT and ABC subpopulations but improved outcomes with manageable safety in patients <60 years, consistent with overall PHOENIX study outcomes.